The economic ethics of Calvinism. The reconciliation of piety and wealth - Chmielewska, Lucyna (Annales. Etyka w Życiu Gospodarczym, 2019)
The doctrine of predestination in the Lutheran and Calvinist theology, along with the assumption of a radical separation of nature and grace as well as the material and spiritual realm, had a significant impact on social life. The salvation of the soul, the soteriological dimension of human destiny, remained dependent on the grace of God (predestination), undeserved and unfathomable. The earthly reality, the institution of the Church and good works could in no way contribute to the salvation of the soul. Martin Luther, especially at the initial stage of his reformation activities, focused on private spirituality, considering the earthly dimension of reality to be the domain of the secular power. John Calvin and his successors justified in their teachings a different attitude manifested in the interest in the earthly world based on religious ethics. The doctrine of predestination, therefore, did not result in, as one would expect, quietism but in activism. The Calvinists believed that predestination was not manifested in single good deeds but in a certain methodology of systematised life based on religious ethics. Religiousness was supposed to be expressed through activity in the world and was meant to show the glory of its Creator. Work, thrift and honesty were supposed to lead to the rebirth, i.e. “sanctification” of the world, and were the essence of what Max Weber called the spirit of capitalism. Calvinism led to changes in the approach to such economic issues as money lending at interest, work or enrichment.